2018
DOI: 10.1038/s41598-018-23720-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of glutamine synthetase-mediated selection for the establishment of recombinant CHO cells producing monoclonal antibodies

Abstract: To characterize a glutamine synthetase (GS)-based selection system, monoclonal antibody (mAb) producing recombinant CHO cell clones were generated by a single round of selection at various methionine sulfoximine (MSX) concentrations (0, 25, and 50 μM) using two different host cell lines (CHO-K1 and GS-knockout CHO). Regardless of the host cell lines used, the clones selected at 50 μM MSX had the lowest average specific growth rate and the highest average specific production rates of toxic metabolic wastes, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 41 publications
5
63
0
Order By: Relevance
“…host cell line. 22,23 With the use of a low amount of 25 μM MSX on CHO-K1SV GS −/cells, the bulk culture productivity was doubled when compared to parental CHO-K1SV cells. The efficiency of finding high-producing clones (>2g/L) was increased sixfold.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…host cell line. 22,23 With the use of a low amount of 25 μM MSX on CHO-K1SV GS −/cells, the bulk culture productivity was doubled when compared to parental CHO-K1SV cells. The efficiency of finding high-producing clones (>2g/L) was increased sixfold.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the GS selection system in CHO cells has previously been evaluated. 23,25,35,36 Evaluation of high-producing GS-selected clones demonstrated that instability stems from promoter silencing, antibody gene copy loss, and generation of secondary poor-producing populations. 25,36 Gene copy loss could be due to unstable chromosomal structures, as shown previously in GS-selected CHO cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the interconnected nature of transport of amino acids, such an effect of serine may be observed to varying effects in different medium formulations. For the commercially important GS‐CHO and GS‐NS0 cell lines which are cultivated in the absence of glutamine, this is an important observation in the context of the design of culture medium and feed. Supplementation of glutamine for culture of GS‐CHO to control culture pH and reduce lactate generation is also reported and the results reported in this study will be relevant in such cases.…”
Section: Discussionmentioning
confidence: 99%